2016
DOI: 10.1016/j.advwatres.2016.03.019
|View full text |Cite
|
Sign up to set email alerts
|

On the non-uniqueness of the hydro-geomorphic responses in a zero-order catchment with respect to soil moisture

Abstract: This study advances mechanistic interpretation of predictability challenges in hydrogeomorphology related to the role of soil moisture spatial variability. Using model formulations describing the physics of overland flow, variably saturated subsurface flow, and erosion and sediment transport, this study explores (1) why a basin with the same mean soil moisture can exhibit distinctly different spatial moisture distributions, (2) whether these varying distributions lead to non-unique hydro-geomorphic responses, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 84 publications
(94 reference statements)
1
14
0
Order By: Relevance
“…A first-order priority for land surface models (LSMs) is accurately capturing the degree to which prestorm soil moisture levels constrain event runoff coefficients (Koster & Milly, 1997; i.e., the fraction of rainfall accumulation volume converted into stormflow during a storm event). The relationship between prestorm soil moisture and hydrologic basin response has received considerable attention in small-scale field studies (e.g., Western & Grayson, 1998) and the development of hydro-geomorphologic models capable of capturing the coupled relationship between stormflow, erosion, and sediment transport (e.g., Kim et al, 2016). Such work has contributed to an improved understanding of the complex role soil moisture plays in various runoff generation processes (e.g., Mirus & Loague, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A first-order priority for land surface models (LSMs) is accurately capturing the degree to which prestorm soil moisture levels constrain event runoff coefficients (Koster & Milly, 1997; i.e., the fraction of rainfall accumulation volume converted into stormflow during a storm event). The relationship between prestorm soil moisture and hydrologic basin response has received considerable attention in small-scale field studies (e.g., Western & Grayson, 1998) and the development of hydro-geomorphologic models capable of capturing the coupled relationship between stormflow, erosion, and sediment transport (e.g., Kim et al, 2016). Such work has contributed to an improved understanding of the complex role soil moisture plays in various runoff generation processes (e.g., Mirus & Loague, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They also found that this nonuniqueness in the erosive response was due to the first storm resulting in different compositions of the deposited layer (or initial conditions) prior to the start of the second storm. Kim et al [2016b] also demonstrated the role of the subsurface initial moisture content in causing nonunique sediment transport under the same rainfall history. Numerical simulations reported by Kim et al [2016a] on total sediment loss at the plot scale provide evidence (their supporting information Figure S2) of the dependence of clockwise and counter-clockwise hysteresis loops on the initial state of the deposited layer.…”
Section: Publicationsmentioning
confidence: 86%
“…Real-time forecasting is an important component of flood risk management and mitigation but is subject to multiple uncertainties caused by meteorological inputs, initial states, model structures, and model parameters (Ajami et al, 2007;Beven, 1989;Mockler et al, 2016;Moradkhani & Sorooshian, 2008). Due to the complexities of natural phenomena represented by equifinality (Beven, 2006;Beven & Freer, 2001), hysteresis (Fatichi et al, 2015;Ivanov et al, 2010;Wei & Dewoolkar, 2006), nonuniqueness (Beven, 2000;McKenna et al, 2003;Kim & Ivanov, 2014;Kim, Dwelle, et al, 2016), nonlinearity (Kim & Ivanov, 2015;Kitanidis & Bras, 1980;Xie & Zhang, 2010), and internal variability (Kim et al, 2016a(Kim et al, , 2016bKim et al, 2018;Lafaysse et al, 2014;Mondal & Mujumdar, 2012;Nikiema & Laprise, 2011), perfect predictions using numerical models are infeasible. The problem exacerbates, if one attempts to simulate constitutive models derived from empirical or phenomenological observations rather than basic conservation laws of physics that would also require embracing a large number of parameters.…”
Section: Introductionmentioning
confidence: 99%